Pyrolysis of organic molecules : applications to health and environmental issues - Moldoveanu, Serban (Elsevier, 2019)
Pyrolysis of Organic Molecules: Applications to Health and Environmental Issues, Second Edition offers a systematic presentation of pyrolysis results for the main classes of non-polymeric organic molecules. It covers a large body of data published on pyrolysis, as well as numerous original contributions to the pyrolysis of compounds not previously studied. This thoroughly revised edition contains new results reported in the literature since the first edition published, including the generation of traces of toxic compounds in various pyrolytic processes; the pyrolysis in the presence of catalysts and solid supports such as alumina, silica, and non-inert metals; and pyrolysis of specific mixtures of compound such as amino acids plus carbohydrates. This new information regarding the pyrolysis of these mixtures has greatly improved the utility of the book, making Pyrolysis of Organic Molecules an essential resource for chemists and chemical engineers involved in processes related to pyrolysis, as well as toxicologists and environmentalists.